Gambaran Cemaran dan Kadar Metil Galat pada Tiga Mutu Ekstrak Gambir (Uncaria gambir Roxb.) - Alegantina, Sukmayati; Setyorini, Herni Asih (Jurnal Kefarmasian Indonesia, 2017)
Gambir (Uncaria gambirRoxb) is a plant that has many benefits to health such as antioxidants, antihiperlipidemiaandantibacterial. Gambir extract derived from the leaves and twigs of Uncaria gambirRoxb through the process of removing the sap by being boiled, squeezed / compressed, liquid is deposited, molded and dried. During the plant grows, then harvest, process, stored and distributed, it is might contaminated with microbes or chemicals. Based on the requirement issued by BPOM No. 12, 2014 about Traditional Medicine Quality Requirements, it requires us to test the extract that we will use. To determine the contaminant of all three gambir extracts, we tested against yeast fungi figures, total plate count, aflatoxin and heavy metals. Besides that, we also determine content of active compound of methyl gallate which has benefits as an antioxidant with a densitometer. the result shows, there werecontaminants that exceeded the requirements. Contaminants that exceeds the requirement are number of fungi yeasts (7,5.10-6) and aflatoxin G2 (47,38.106ppb) in gambier extract quality 3. The highest content of active compound of methyl gallate was obtained from extracts of gambir quality 3 (2.30%) followed by gambir quality 2 (0.44%) and gambir quality1 (0.14%).